Immigrants in the British Labour Market - Christian Dustmann; Francesca Fabbri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2005)
The main objective of this paper is to provide a comprehensive description of the economic outcomes and performance of Britain's immigrant communities today and over the last two decades. We distinguish between males and females and, where possible and meaningful, between immigrants of different origin. Our comparison group are white British born individuals. Our data source is the British Labour Force Survey (LFS). We first provide descriptive information on the composition of immigrants in Britain, and how this has changed over time, their socio-economic characteristics, their industry allocation, and their labour market outcomes. We then investigate various labour market performance indicators (labour force participation, employment, wages, and self-employment) for immigrants of different origin, and compare them to British-born whites of same age, origin, and other background characteristics. We find that over the last 20 years, Britain's immigrant population has changed in origin composition, and has dramatically improved in skill composition - not dissimilar from the trend in the British born population. We find substantial differences in economic outcomes between white and ethnic minority immigrants. Within these groups, immigrants of different origin differ considerably with respect to their education and age structure, their regional distribution, and sector choice. In general, white immigrants are more successful in Britain, although there are differences between groups of different origin. The investigation shows that immigrants from some ethnic minority groups, and in particular females, are particularly disadvantaged, with Pakistanis and Bangladeshis at the lower end of this scale.
Keywords: J15; 330; International Migration; Economic Performance